Strategic Kaizen TM Using Flow, Synchronization and Leveling [FSL TM] Assessment to Measure and Strengthen Operational Performance - Imai, Masaaki 1930- (McGraw Hill, 2021)
"The groundbreaking follow-up from the bestselling author of Gemba Kaizen, and pioneer of "continuous improvement" operational excellence. Whether you run a business or practice Lean, this groundbreaking guide provides everything you need to transform your company in measurable ways. The founder of the Kaizen Institute, Masaaki Imai introduces his revolutionary Flow, Synchronization, and Leveling Assessment (FSLA)-a first-of-its-kind Lean paradigm for measuring and improving operational performance. This new business classic teaches you: The importance of assessing corporate performance from both the financial and operational standpoints How to identify basic structures of the ideal production systems Proven ways of implementing FSLA to both measure operational performance and drive cost-effective, incremental improvements in their most critical business processes"--
Keywords: Total quality management; Continuous improvement process; Organizational effectiveness; Organizational change